Analisis Faktor Internal dan Eksternal Akuntansi Emisi Karbon: (Studi Empiris Pada Perusahaan Manufaktur di Sektor Aneka Industri Yang Terdaftar di Bursa Efek Indonesia Pada Tahun 2021-2023) - Afriska Oktavia; Aida Nahar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
Global warming and the environmental impact of manufacturing activities are hot topics in Indonesia, where air quality ranks highest in Southeast Asia in 2024. The purpose of this study is to empirically test and determine whether internal and external factors, namely leverage, liquidity, profitability, regulation, carbon tax, and environmental performance, affect carbon emissions accounting in manufacturing companies in the miscellaneous industry sector listed on the Indonesia Stock Exchange in 2021-2023. The analytical methodology applied includes descriptive statistical analysis and multiple linear regression analysis using SPSS 25 software and involves 60 observations selected using purposive sampling. The results of the study show that leverage, profitability, and regulation have a positive and significant effect on carbon emissions accounting. Conversely, liquidity and carbon tax have a negative and significant effect on carbon emissions accounting, while environmental performance has no effect on carbon emissions accounting. This study confirms the key role of financial and regulatory factors in improving carbon emissions transparency. The implications of this study are that entities need to optimize leverage and profitability for carbon reporting transparency, mitigate liquidity and carbon tax risks, and strengthen regulations to support sustainability accounting.